Politik Hukum Pengaturan Ahli Waris Pengganti dalam Pasal 185 Kompilasi Hukum Islam: Analisis Normatif dan Implikasinya Terhadap Sistem Kewarisan di Indonesia - Asep Fu’ad; Aden Rosadi; Usep Saepullah; Husain (al-Battar: Jurnal Pamungkas Hukum, 2024)
This research aims to analyze the concept of substitute heirs in Article 185 of the Compilation of Islamic Law (KHI) and its implications for the inheritance system in Indonesia. This research uses a normative juridical method with a legal political approach. This approach is used to explore the legal and policy background behind the arrangement of substitute heirs in KHI. The results show that although classical Islamic law, especially the Syafi'i school, does not recognize the concept of substitute heirs, KHI adopts a more inclusive approach. Article 185 of the KHI grants inheritance rights to descendants of heirs who have died before the testator, which is a political legal effort to achieve social justice in the context of Indonesian inheritance. Although this arrangement aims to create social justice, findings show that there are challenges in its acceptance in the community. Many Indonesians still hold strong customs and traditional understandings in the inheritance system. Therefore, more intensive socialization is needed to bridge the gap between the positive law and the local community's understanding of the prevailing inheritance system.